Multi-Frequency and Multi-Polarization Synthetic Aperture Radar for the Larsen-C A-68 Iceberg Monitoring - Nunziata F.; Buono A.; Migliaccio M.; Moctezuma M.; Parmiggiani F.; Aulicino G. (2018 IEEE 4th International Forum on Research and Technology for Society and Industry (RTSI), 2018)
Since 2016 the fracture of the Larsen-C ice shelf has been regularly observed in the Eastern Weddell Sea (68°S, 61°W, Antarctica). This process led to the final collapse in July 2017, when an area of about 6000 km 2 (i. e., about 9-12% of the whole shelf) was lost. In this study the resulting calved iceberg, termed as 'A-68' from the U. S. National Ice Center, is observed using multi-frequency and multi-polarization Synthetic Aperture Radar (SAR) satellite platforms that include L-band Alos PaISAR-2, C-band Sentinel-l and X-band COSMO-SkyMed. A large set of SAR scenes were considered, collected in ScanSAR imaging modes over a time span of about 1 year, to analyze the iceberg properties and its melting process and drifting.